The effect of heat mitigation strategies on thermoregulation and productivity during simulated occupational work in the heat in physically active young men - Morrissey-Basler, Margaret C.; Brewer, Gabrielle J.; Anderson, Travis; Adams, William M.; Navarro, John S.; Marcelino, Monique; Martin, David G.; Casa, Douglas J. (Frontiers in Sports and Active Living, 2024)
Purpose To investigate heat stress mitigation strategies on productivity and thermoregulatory responses during simulated occupational work in the heat. Methods Thirteen physically active men (age, 25 ± 4 years; body mass,77.8 ± 14.7 kg; VO2peak, 44.5 ± 9.2 ml·kg−1·min−1) completed five randomized-controlled trials in a hot environment (40°C, 40% relative humidity). Each trial was 4.5 h in duration to simulate an outdoor occupational shift. Thermoregulatory responses (heart rate, HR; rectal temperature, Trec; mean skin temperature, Tsk), perceptual responses (rating of perceived exertion, RPE; thermal sensation; thermal comfort; fatigue) and productivity outcomes (box lifting repetitions, time to exhaustion) were examined in the following heat mitigation strategy interventions: (1) simulated solar radiation with limited fluid intake [SUN]; (2) simulated solar radiation with no fluid restrictions [SUN + H2O]; (3) shade (no simulated solar radiation during trial) with no fluid restrictions [SHADE + H2O]; (4) shade and cooling towels during rest breaks with no fluid restrictions [COOL + H2O]; and (5) shade with cooling towels, cooling vest during activity with no fluid restrictions [COOL + VEST + H2O]. Results [COOL + VEST + H2O] had lower Trec compared to [SUN] [p = 0.004, effect size(ES) = 1.48], [SUN + H2O] (p < 0.001, ES = −1.87), and [SHADE + H2O] (p = 0.001, ES = 1.62). Average Tsk was lower during the treadmill and box lifting activities in the [COOL + VEST + H2O] compared to [SUN] (p < 0.001, ES = 7.92), [SUN + H2O] (p < 0.001,7.96), [SHADE + H2O] (p < 0.001), and [COOL + H2O] (p < 0.001, ES = 3.01). There were performance differences during the [COOL + VEST + H2O] (p = 0.033) and [COOL + H2O] (p = 0.023) conditions compared to [SUN] during phases of the experimental trial, however, there were no differences in total box lifting repetitions between trials (p > 0.05). Conclusion Our results suggest that during a simulated occupational shift in a laboratory setting, additional heat mitigation strategies ([COOL + VEST + H2O] and [COOL + H2O]) reduced physiological strain and improved box lifting performance to a greater degree than [SUN]. These differences may have been attributed to a larger core to skin temperature gradient or reduction in fatigue, thermal sensation, and RPE during [COOL + H2O] and [COOL + VEST + H2O]. These data suggest that body cooling, hydration, and “shade” (removal of simulated radiant heat) as heat stress mitigation strategies should be considered as it reduces physiological strain while producing no additional harm.